A model for the prediction of print quality of a roll-to-roll inkjet press - Norrick, Nicklas (Journal of Print and Media Technology Research, 2023)
In this paper, a simulation model for the web dynamics of a digital label printing machine is presented and an exemplary application from practice is shown to verify the model. The basis is an extended modeling of the web dynamics including thermal effects in order to calculate the dynamic behavior of the continuous web. It is shown how thermal excitation can be used to measure the transfer function of the web dynamics and the influence of web tension control systems. Furthermore, a post-processing algorithm is presented which links the output data of the web dynamics simulation with the behavior of the inkjet printing data path and thus simulates digital inkjet printing. The results can be used to explain both registration errors from color to color as well as color density fluctuations within a raster image printed by a single color. As a practical example, a digital inkjet printing machine is considered in the following, in which a periodic variation in the color impression of a raster or solid surface can be recognized in the printed image. The fluctuation period corresponds to one revolution of the rotary encoder, which serves as a trigger signal for the inkjet printheads. With the help of the simulation model for the web dynamics and the presented post-processing algorithm, the origin of the error can be understood. Measurement and simulation are compared to verify the model. If the amplitude and the phase angle of the encoder error are measured, the print quality can be ensured by compensating the error within the inkjet printing data path. This is shown both in the simulation and on the basis of measured data.